2017
DOI: 10.1007/s40940-017-0039-4
|View full text |Cite
|
Sign up to set email alerts
|

The construction of the Crystal Houses façade: challenges and innovations

Abstract: A novel glass brick façade has been designed and engineered to reproduce the original brick façade of a former townhouse in Amsterdam. Based on the original design the resulting façade comprises more than 6500 solid glass bricks, reinterpreting the traditional brick pattern, and elaborated cast glass elements for the replication of the window and door frames. To achieve unhindered transparency, the 10 by 12 m glass block façade has to be self-supporting. Previous experimental work by Oikonomopoulou et al. (J F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 10 publications
0
41
0
Order By: Relevance
“…There, a commonly used material is the so‐called UV‐cured adhesive polymer (Figure ). Because of their typical thickness and low viscosity, the fabrication process of UV‐bonded adhesive connections can be rather complex and often requires and experience workmanship and dedicated tools . Several research works can be found in literature on UV‐cured adhesive connections.…”
Section: Existing Research On Small‐scale Components and Materialsmentioning
confidence: 99%
“…There, a commonly used material is the so‐called UV‐cured adhesive polymer (Figure ). Because of their typical thickness and low viscosity, the fabrication process of UV‐bonded adhesive connections can be rather complex and often requires and experience workmanship and dedicated tools . Several research works can be found in literature on UV‐cured adhesive connections.…”
Section: Existing Research On Small‐scale Components and Materialsmentioning
confidence: 99%
“…Delo Photobond 4468, a one-component, clear, UV-curing acrylate, was selected for bonding the elements together due to its colourless nature, similar refraction index to glass, fast application and very good mechanical properties (Delo Industrial Adhesives 2014). The specific adhesive was also applied in the construction of the Crystal Houses façade in Amsterdam (Oikonomopoulou et al 2017). 4-point bending experiments on glass beams consisting of adhesively bonded solid glass bricks by Oikonomopoulou et al (2015a) demonstrated the monolithic behaviour of the glass-adhesive assembly under loading.…”
Section: Design Concept and Production Considerationsmentioning
confidence: 99%
“…In the A 1 series, with to the central star profile present, the adhesive can be easily applied along the whole length of the rods in a consistent layer of circa 0.2-0.3 mm thickness. Oikonomopoulou et al (2017) states this thickness as providing the optimum bonding strength of the specific adhesive and argues on why a thicker adhesive joint has a negative effect in the structural performance of the glass-adhesive assembly. In the case of the A 2 specimens, the geometry of the triple bundle without core results in a significantly thicker and inconsistent adhesive layer at its centre.…”
Section: Testing Of a 2 Series: Evaluation Of The Influence Of Splicementioning
confidence: 99%
“…In most of these realizations the bricks do not fulfill the load-bearing function so additional supporting structure is needed. An exception is the Crystal House in Amsterdam (Oikonomopoulou, Bristogianni, Veer, & Nijsse, 2017) and the Atocha Monument in Madrid (Christoph & Knut, 2008). These projects use custom-made bricks, whose price is undoubtedly higher than in mass production.…”
Section: Introductionmentioning
confidence: 99%